2017
DOI: 10.1016/j.ram.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of lepidopteran-specific toxin genes in Bacillus thuringiensis strains from Argentina

Abstract: A total of 268 Bacillus thuringiensis strains obtained from different sources of Argentina were analyzed to determine the diversity and distribution of the cry1, cry2, cry8, cry9 and vip3A genes encoding for lepidopteran-specific insecticidal proteins. Twin strains were excluded. Ten different profiles were detected among the 80 selected B. thuringiensis strains. Two of these profiles (cry1Aa, cry1Ac, cry1Ia, cry2Aa, cry2Ab and vip3Aa (35/80), and cry1Aa, cry1Ab, cry1Ac, cry1Ia, cry2Aa, cry2Ab and vip3Aa (25/8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
2
9
0
3
Order By: Relevance
“…5 Larvicidal activity of B. thuringiensis against S. litura larvae. Error bar indicates ± standard error for three experiments frequencies of gene combinations in our B. thuringiensis collection, as 19 gene profiles were observed which were higher than that reported in Argentina where 10 gene combination profiles were reported (Sauka and Benintende 2017). However, higher numbers of cry gene combination profiles (43 profiles) were reported for cry1 subclasses of B. thuringiensis from China (Wang et al 2003).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…5 Larvicidal activity of B. thuringiensis against S. litura larvae. Error bar indicates ± standard error for three experiments frequencies of gene combinations in our B. thuringiensis collection, as 19 gene profiles were observed which were higher than that reported in Argentina where 10 gene combination profiles were reported (Sauka and Benintende 2017). However, higher numbers of cry gene combination profiles (43 profiles) were reported for cry1 subclasses of B. thuringiensis from China (Wang et al 2003).…”
Section: Discussionmentioning
confidence: 51%
“…The SEM images showed bipyramidal and cuboidal crystal morphologies of B. thuringiensis 225-15, 349-4, 417-1, 831-2, and 834-1 that were similar to most of the B. thuringiensis samples in Argentina, of which 88.8% of isolates containing cry1 and cry2 genes exhibited bipyramidal and cuboidal crystals (Sauka and Benintende 2017). The inclusion morphologies of B. thuringiensis serovar kurstaki HD1 have been reported to be bipyramidal and cuboidal structures (Monnerat et al 2007;Patel et al 2012;Zorzetti et al 2017); however, some publications reported that this strain contained bipyramidal, cuboidal, and spherical structures (Azizoglu et al 2015;Yılmaz et al 2012).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Estas plantas resistentes a insectos se obtienen a partir de modificaciones genéticas consistentes en la introducción de un gen que codifica la síntesis de toxinas proteicas pertenecientes a distintas cepas de B. thuringiensis (Siebert et al, 2008;Tabashnik et al, 2009;Casmuz et al, 2010;James, 2012). Las propiedades insecticidas de B. thuringiensis son atribuidas principalmente a la síntesis de cristales proteicos insecticidas (toxinas Cry) y a proteínas insecticidas vegetativas (toxinas Vip), las cuales son producidas por la bacteria durante la fase de esporulación o crecimiento vegetativo, respectivamente (Pigott et al, 2008;Palma et al, 2012;Sauka & Benintende, 2017). El ciclo de vida de B. thuringiensis se divide en cuatro fases.…”
Section: 4) Manejo De Spodoptera Frugiperda En Maízunclassified